CORPUS EPOCHALIS. MYSTICISM, BODY, HISTORY - Mihailescu, Calin (Surfaces, 1991)
The discourse of the body and history in the mystical tradition, especially Pascal. De Certeau on the history of Mysticism, Deleuze and Guattari on the body.